Vitrectomy using 0.025% povidone-iodine irrigation for treating post-traumatic endophthalmitis due to intraocular foreign bodies: Two case reports - Liu, Chi; Xu, Ke; Hu, Ying; Zhuang, Xiaotong; Fu, Bo; Wang, Lin; Jia, Xinzhu; Xu, Li (Frontiers in Surgery, 2023)
Traumatic eye injury related endophthalmitis is a serious traumatic complication, and this threatens the vision of many patients worldwide. Herein, we presented two cases with traumatic endophthalmitis underwent 0.025% povidone-iodine treatment and hope to introduce the bactericidal effect of 0.025% povidone-iodine in Balanced Salt Solution PLUS (0.025% PI-BSS PLUS) and its use in vitrectomy for traumatic endophthalmitis. The 0.025% PI–BSS PLUS is bactericidal and nontoxic when used as irrigation solution in pars plana vitrectomy. In two cases of traumatic endophthalmitis, pars plana vitrectomy using 0.025% PI–BSS PLUS resolved endophthalmitis.